Evaluation of the Definitions of "High-Risk" Cutaneous Squamous Cell Carcinoma Using the American Joint Committee on Cancer Staging Criteria and National Comprehensive Cancer Network Guidelines. (16th September 2014) - Chu, Melinda B.; Slutsky, Jordan B.; Dhandha, Maulik M.; Beal, Brandon T.; Armbrecht, Eric S.; Walker, Ronald J.; Varvares, Mark A.; Fosko, Scott W.
Abstract : Recent guidelines from the American Joint Committee on Cancer (AJCC) and National Comprehensive Cancer Network (NCCN) have been proposed for the assessment of "high-risk" cutaneous squamous cell carcinomas (cSCCs). Though different in perspective, both guidelines share the common goals of trying to identify "high-risk" cSCCs and improving patient outcomes. Thus, in theory, both definitions should identify a similar proportion of "high-risk" tumors. We sought to evaluate the AJCC and NCCN definitions of "high-risk" cSCCs and to assess their concordance. Methods . A retrospective review of head and neck cSCCs seen by an academic dermatology department from July 2010 to November 2011 was performed. Results . By AJCC criteria, most tumors (n = 211, 82.1 %) were of Stage 1; 46 tumors (13.9%) were of Stage 2. Almost all were of Stage 2 due to size alone (≥2 cm); one tumor was "upstaged" due to "high-risk features." Using the NCCN taxonomy, 231 (87%) of tumors were "high-risk." Discussion . This analysis demonstrates discordance between AJCC and NCCN definitions of "high-risk" cSCC. Few cSCCs are of Stage 2 by AJCC criteria, while most are "high-risk" by the NCCN guidelines. While the current guidelines represent significant progress, further studies are needed to generate a unified definition of "high-risk" cSCC to optimize management.